ANALISIS PENGGUNAAN BUKU DIGITAL KATEGORI B2 TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS II SD MENGGUNAKAN PENDEKATAN DEEP LEARNING - Agustianingrum, Ajeng; Aryanto, Sani; Awiria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of using Digital Books Category B2 through the Deep Learning Approach in improving reading comprehension skills of second-grade elementary school students. The main issue raised is the gap between technical reading skills (decoding) and understanding of deep meaning during the literacy transition phase. Using a descriptive qualitative approach, the study involved 30 second-grade students in the 2025/2026 academic year. Data were collected through observation, interviews, and assessment of learning outcomes regarding the use of the digital media "Kotak Petualang". Data analysis was carried out in a circular manner including data reduction, presentation, and verification. The results showed a collective success rate of 90%, with details of 25 students (83.3%) in the high category, 2 students (6.7%) in the medium category, and 3 students (10.0%) in the low category. The expressive read-aloud strategy and interactive features of digital books proved effective as scaffolding for students in constructing both literal and reflective understanding. Although effective in increasing interest and engagement, students in the low category still require intensive guidance to achieve independent critical thinking skills. In conclusion, the synergy of Digital Books B2 and Deep Learning can transform literacy learning to be more immersive and meaningful. This integration is a strategic solution to reduce students' cognitive barriers in the digital age.